(Re)conceptualising Children's Rights in Infant-Toddler Care and Education Transnational Conversations - Press, Frances; Cheeseman, Sandra (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book brings together researchers from a variety of national contexts to examine and explore the conceptualisation, reconceptualisation and translation of children's rights for infants and toddlers in early childhood education and care settings.It brings together authors from various national contexts to examine changing understandings and manifestations of infant and toddler rights in Early Childhood Education and Care. The book aims to engender trans-national dialogue through the contributions. Through such dialogue, both authors and readers are challenged to recognise the specificity of their own cultural contexts and thereby envision a more expansive view of infant and toddler rights. By drawing together reflections on infant-toddler rights from key early childhood researchers across the world, this book will extend readers understandings of rights - not only in terms of how rights are (re)conceptualised but also how to meaningfully translate the rights afforded in policy to practice.
Chapter 1. Conceptualising and reconceptualising infant-toddler rights in a changing early childhood landscape (Frances Press) -- Chapter 2. Children's rights education for the Early Childhood Education and Care student (Sheila Long) -- Chapter 3. Fledgling Embeddedness of Child Rights Education into Early Childhood Education and Care Undergraduate Programs in Chile: Are There Any Possibilities for the Enactment of Infants' and Toddlers' Rights in ECEC centers? (Marcela Pardo) -- Chapter 4. Commentary on Chapters 2 and 3. Our Future Teachers-Duty Bearers, Activists and Advocates (Linda Mitchell) -- Chapter 5. Infants' and toddlers' rights in early childhood settings: Research perspectives informing pedagogical practice (Andi Salamon) -- Chapter 6. Reconceptualising Shier's pathways to participation with infants: Listening and responding to the views of infants in their encounters with curriculum (Sandra Cheeseman) -- Chapter 7. Commentary: Chapters 5 & 6: How Does a Contract Between the Generations Guide our Work as Researchers or Educators? (Niina Ruttanen) -- Chapter 8. Making the Voice of the Child Visible Documenting and Fostering Language from a Children's Rights Perspective (Andrea Tures) -- Chapter 9. A Right to Know: The Positioning of Infants as Knowers in Educator-Infant Interactions (Sheila Degotardi) -- Chapter 10. Commentary Chapters 8 & 9: Supporting Communication Practices: Beyond the Focus on the Child (Martina Street) -- Chapter 11. Communication Rights of Young Children in Early Childhood Education and Care (Anna Cronin) -- Chapter 12. The Rights of the Toddler: The Complexities of Supporting Young Children's Becoming and Belonging in an Inclusive Classroom Community (Susan L. Recchia) -- Chapter 13. Commentary Chapter 12: Finding Voice in Practices (Deborah James) -- Chapter 14. Beyond the tangible, towards the invisible: Reflecting on the rights and realities of infants and toddlers living in an underprivileged context in Mumbai, India (Sanobia Palkhiwala) -- Chapter 15. The Child's Right to Love in Early Learning and Childcare A Scottish Perspective (Jane Malcolm) -- Chapter 16. Commentary Chapter 14 & 15: Contradictions and Challenges About Enacting Infant-Toddler Rights in Diverse Political, Cultural and Policy Contexts (Linda J. Harrison).
Keywords: Early childhood education; Education and state; Educational sociology; Early Childhood Education; Educational Policy and Politics; Sociology of Education